Study on interfacial reaction behavior of SnAg based lead-free solder with (111) single crystal copper substrate. (December 2022) - Han, Jing; Meng, Zhou; Jin, Xuelun; Ma, Limin; Guo, Fu; An, Tong; Wang, Ting; Zhou, Wei
Abstract: The morphology and crystal orientation of intermetallic compounds formed by the reaction between SAC305 solder/(111) and SABI333 solder/(111) single crystal copper substrate were investigated. The morphology of Cu6 Sn5 at the interface of SAC305 solder/(111) single crystal copper substrate changes from scallop to prismatic with the increase of reflow time. The Cu6 Sn5 grains grow parallel to the horizontal direction of the Cu substrate and grow along the vertical direction, and there is an Angle of 60° between different Cu6 Sn5 crystals. The calculated b ~ t 0.23 relation satisfies the growth kinetics of prismatic Cu6 Sn5 . In addition, the morphology of Cu6 (Sn, In)5 at the interface of SABI333 solder/(111) single crystal copper substrate is between scallop-type and prismatic-type. Cu6 (Sn, In)5 grains grow at a certain angle with a single crystal copper substrate due to the addition of In element. Furthermore, it is considered that the deflection mechanism of Cu6 (Sn, In)5 grains is controlled by the length and strength of inter-atomic bonds within the grains after the In atom substitution reaction. Highlights: The mechanism of IMCs growth of SAC305 solder on single crystal copper is proposed. The mechanism relies on the length of reflux time and satisfies b ~ t 0.23 . The IMCs Cu6 (Sn, In)5 of SABI333 solder grows at an angle with the substrate. The deflection mechanism of Cu6 (Sn, In)5 is proposed. This mechanism relies on the inhomogeneity of In atoms replacing Sn atoms.